Institutions, Sustainability, and Natural Resources Institutions for Sustainable Forest Management - Kant, Shashi; Berry, R. Albert; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2005)
A new economic theory, rather than a new public policy based on old theory, is needed to guide humanity toward sustainability. Institutions are a critical dimension of sustainability and sustainable forest management, and economic analysis of institutional dimension requires an inclusionist rather than an exclusionist approach. This book provides a systematic critique of neoclassical economic approaches and their limitations with respect to sustainability. Leading institutional economists discuss theoretical perspectives about appropriate institutions for sustainable forest management, markets for environmental services, deforestation and specialization, and some country experiences about Kyoto Protocol, international trade, biodiversity conservation, and sustainable forest management in general. The book includes the ideas from old as well as new institutional economics and discusses the main features of Post-Newtonian economics. This book follows a companion book, Economics, Sustainability, and Natural Resources: Economics of Sustainable Forest Management, volume 1 of the series.
Sustainability, Institutions, and Forest Management -- Epilogue -- Institutions, Sustainable Forest Management, and Post-Newtonian Economics -- In Search of Optimal Institutions for Sustainable Forest Management: Lessons from Developed and Developing Countries -- Modern Economic Theory and the Challenge of Embedded Tenure Institutions: African Attempts to Reform Local Forest Policies -- Organizations, Institutions, External Setting and Institutional Dynamics -- Valuing Forest Ecosystems - An Institutional Perspective -- The Great Tragedy of Science: Sustainable Forest Management and Markets for Environmental Services -- The Kyoto Protocol: Property Rights and Efficiency of Markets -- Deforestation and Population Increase -- Limitations of Sustainable Forest Management: An Economics Perspective -- Sustainable Forestry in a World of Specialization and Trade -- Forest Carbon Sinks: A Temporary and Costly Alternative to Reducing Emissions for Climate Change Mitigation -- The International Trade and Environmental Regime and the Sustainable Management of Canadian Forests -- Sustainable Forest Management: Ciriacywantrup's Definition of Conservation in Today's Forest Resource Context -- Stakes, Suspicions and Synergies in Sustainable Forest Management-the Asian Experience.
Keywords: ECONOMICS; FORESTS AND FORESTRY; ENVIRONMENTAL MANAGEMENT; ECONOMIC POLICY; ENVIRONMENTAL ECONOMICS; COMMERCIAL LAW; ECONOMICS/MANAGEMENT SCIENCE; ENVIRONMENTAL ECONOMICS; ECONOMICS/MANAGEMENT SCIENCE, GENERAL; LAW AND ECONOMICS; FORESTRY MANAGEMENT; ECONOMIC POLICY; ENVIRONMENTAL MANAGEMENT